T150. A case of anti-VGKC antibody negative acquired peripheral nerve hyperexcitability. (May 2018) - Lefter, Stela; Moore, Helena; McNamara, Brian; Fanning, Noel; Connolly, Sean
Abstract : Introduction: Neuronal hyperexcitability can cause spontaneous muscle activity. When acquired this is often, but not always, associated with antibodies against voltage-gated potassium channels (anti-VGKC). Methods: A 53 year-old man was referred for an electrodiagnostic evaluation with a 5-month history of progressive lower limb symptoms. These began as numbness in the right foot that progressed to affect both feet over a 3-month period. Over the following 2 months he developed tingling to the shins and later the abdomen, "feeling of sunburn" in the thighs and lower abdomen triggered by movement, difficulty walking and painful cramping of feet and legs, more marked on the right side. He denied weakness in the lower limbs, upper limb symptoms or sphincter disturbance. He was a non-smoker. Medical history was clear apart from borderline hypertension. Cranial nerves and upper limb exam were normal. Examination of the lower limbs revealed: absent deep tendon reflexes throughout, normal tone and power, flexor plantar responses, reduced light touch to T8 level and reduced vibration to the lateral malleoli. Results: Electromyography revealed features compatible with peripheral motor nerve hyperexcitability. Anti-VGKC antibodies were later found to be negative in serum. MRI of thoracic-lumbar spine and Catheter Spinal Angiogram revealed spinal cord oedema due to a right-sided T7 spinal dural arteriovenous fistula (SDAVF). Conclusion: Patient had SDAVF closure with subsequent marked clinical and radiological improvement. Electromyographic findings and interpretation will be presented.